2001
DOI: 10.1021/jo010681w
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Reductive Deamination (Hydrodeamination) of Aromatic Amines

Abstract: Reductive deamination (hydrodeamination) of aromatic amines can be conveniently carried out by amination of the corresponding arylamine methanesulfonamides using chloroamine under alkaline conditions. The intermediate aryl methanesulfonylhydrazines directly eliminate methanesulfinic acid, affording diazenes which extrude nitrogen affording the desired deaminated products. Both sulfonamide formation and reduction reactions occur in high yield and are compatible with a variety of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Using the same procedures, the carbonyl chloride of 9a was reacted with N -(4-hydroxyphenyl)methanesulfonamide 26 to give the target ester derivative 6a ; intermediate 9a was also converted into amino derivative 5a by reaction with 4-nitroaniline followed by catalytic reduction with H 2 /Raney-Ni.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same procedures, the carbonyl chloride of 9a was reacted with N -(4-hydroxyphenyl)methanesulfonamide 26 to give the target ester derivative 6a ; intermediate 9a was also converted into amino derivative 5a by reaction with 4-nitroaniline followed by catalytic reduction with H 2 /Raney-Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Following the general procedure method C and replacing the N -(4-aminophenyl)methanesulfonamide 25 with the N -(4-hydroxyphenyl)methanesulfonamide, 26 compound 6a was obtained from 9a in 65% yield as white solid: mp 252–254 °C. 1 H NMR (400 MHz, DMSO- d 6 ): δ 3.00 (s, 3H, SO 2 CH 3 ), 3.30 (s, 3H, NCH 3 ), 7.00 (d, J = 7.7 Hz, 1H, H-9), 7.25–7.30 (m, 4H, H-2", H-3", H-5" and H-6"), 7.40 (dt, J = 1.0 and 8.0 Hz, 1H, H-8), 7.50 (dt, J = 1.9 and 7.7 Hz, 1H, H-7), 7.55–7.75 (m, 4H, H-2', H-4', H-5', and H-6'), 8.00 (dd, J = 1.0 and 7.7 Hz, 1H, H-6), 9.80 (s, 1H, SO 2 NH).…”
Section: Methodsmentioning
confidence: 99%
“…22,23 A perusal of the literature revealed that sulfonylation of amines with sulfonyl chlorides is commonly performed in pyridine as the base and medium. [24][25][26][27][28] 4-(N,N-Dimethylamino)pyridine (DMAP) is a very good nucleophilic catalyst and is more basic than pyridine. DMAP is widely used as a superb nucleophilic catalyst for many organic reactions such as Baylis-Hillman reaction, 29,30 regioselective acylation of 6-O-protected octyl β-D-glucopyranosides, 31 synthesis of electrophilic alkenes, 32 heroin synthesis, 33 and synthesis of N-sulfonyl monocyclic β-lactams.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the S–N bond in sulfonamides is a much weaker chemical bond, which is more easily broken. In comparison, cleavage of the C–N bond in the N -arylsulfonamides is rare and challenging . Remarkably, Fan and co-workers developed an interesting stepwise oxidative aromaticity destruction–reconstruction process for the cleavage of N -Ts anilines to form a C–C bond (Scheme b) .…”
mentioning
confidence: 99%